The Incidence of Nominal and Real Wage Rigidity : An Individual-Based Sectoral Approach - Messina, Julian; Du Caju, Philip; Duarte, Claudia Filipa; Hansen, Niels Lynggard; Izquierdo, Mario (2012)
This paper presents estimates based on individual data of downward nominal and real wage rigidities for 13 sectors in Belgium, Denmark, Spain, and Portugal. Our methodology follows the approach recently developed for the International Wage Flexibility Project, whereby resistance to nominal and real wage cuts is measured through departures of observed individual wage change histograms from an estimated counterfactual wage change distribution that would have prevailed in the absence of rigidity. Our estimates of wage rigidities are set against structural features of the labour markets studied, including the wage bargaining level and the degree of product market competition.